The Role of the Metaoperator In the Good Sense of the Word in an Idealised Worldview - Vepreva, Irina (Respectus Philologicus, 2012)
This article investigates the functioning of the metaoperator in the good sense of the word, which characterising words, abstracted characteristics of the subject (both animate and inanimate), and appearance. The second type includes utterances where the role of the metaoperator in the good sense of the word neutralises both common and individual negative connotations not included in the conceptual nexus of the word. This type lets the operator, on the one hand, release the individual negative connotations that have appeared in contemporary speech while, on the other hand, it de-ideologizes the lexeme. The article also demonstrates the results of an experiment made, first, to examine the potential possibility of axiological re-coding of any negative word, and second, to estimate a non-estimating word. The experiment gave positive results for both tasks, allowing the author to state that the naive axiology includes the entire world in its estimative perception. The idealised model of the world practically overlaps with the language worldview.
Keywords: metalinguistic utterance; estimation; lexical semantics; pragmatic information; connotation